Olah Produk Tanaman Pisang Dalam Peningkatan Ekonomi Masyarakat Desa Karanglo Kidul Kecamatan Jambon Kabupaten Ponorogo - Asyari, M. Hasyim; Almadani, M. Asip (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Based on the results of the team's survey in Dukuh Tengah, there are potential assets that can be developed, including banana plants. Plants that do not have this season grow a lot in the environment of Dukuh Tengah, therefore in this discussion took the theme with the title